PENDAPATAN PETANI KARET DI GAMPONG PAYA LUMPAT KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Sri Handayani; Aswin Nasution; Matria Gunawan (Jurnal Bisnis Tani, 2018)
Rubber is one of the leading plantation commodities in Aceh Barat besides palm oil, cocoa and patchouli. In addition to natural factors, the willingness of farmers is also one of the most important capital in the development of this commodity. The purpose of this research is to analyze the income of rubber farmers, especially in gampong Paya Lumpat Samatiga District, Aceh Barat. The method used is quantitative descriptive method. The resuls showed that based on the age classification of rubber plants owned by farmers there is a difference in the amount of rubber production and it affects the income received by eachfarmer.